Zur agrargeographischen Gliederung von Haiti - von Koblinski-Siemens, Gundula (ERDKUNDE, 1954)
In 1803, when the slaves in Haiti obtained their freedom, this western part of the island turned into a country of small negro peasant farmers. Whereas formerly, under the rule of the French plantation owners, Haiti provided considerable amounts of plantation crops such as cane sugar, coffee, indigo and cotton for the world market, today agricultural production is on the whole only sufficient for home consumption, the noteworthy exception being coffee. These characteristic Negro peasant holdings (Negerbauernbetriebe) as they were termed by Credner in his paper on types of economic regions in the Greater Antillies (Petermanns Gcographische Mitteilungen, 1943) can here be arranged into certain distinct regional groups. 1. The holdings of the most humid part of the mountains, the Massif de la Hotte, where rainfall exceeds 200 cm. per annum, are characterised by the cultivation of moisture- loving fruit trees: bananas, avocado pears, papaya, bread-fruit trees, coffee and cocoa. 2. In the moderately humid mountains of the northern ranges, the Montagnes Trou d'Eau, which have an annual rainfall of 150—200 cm., cultivation of tree crops is limited to the edaphically humid valley bottoms and spring hollows, whereas the slopes are utilised for growing tropical root crops, sweet potatoes, yautia, yucca, as well as pulses and maize. 3. Outside the area originally covered by tropical rain forest it is impossible to raise tree crops, and these areas, formerly savannas or light deciduous woods, where the annual rainfall ranges from 100—150 cm., are characterised by arable farming proper, i. e. growing of root crops, pulses and maize, supplemented by the keeping of some small livestock such as goats and pigs, whose sustenance is provided by grazing on the fallow. 4. A special position within the former region is occupied by the thinly settled Plateau Centrale where cattle ranching survived from the days whon the plateau belonged to the adjoining Spanish colony of Santo Domingo. Save where irrigation facilities are available, the dry areas with an annual rainfall of less than 100 cm. do not offer any possibilities for subsistence farming, and there we find the Original xerophytic vegetation of the thornbrush woods still preserved. A recent feature in the agricultural economy of Haiti is the emergence of plantations side by side with negro peasant holdings, a process which began in the 'twenties. These plantations, some of which are owned by foreign companies, are found on the alluvial plains and are devoted to the production of cane sugar, copra, sisal, rice and citronella.